IMPACT OF E-BUSINESS ON CHINA WHOLESALE MARKET - shukri, Sakinah mohd; Azam, S.M. Ferdous; Jaharadak, Adam Amril bin (International Journal of Psychosocial Rehabilitation, 2020)
Wholesale market has a significant status in China’s economy. It not only supplies the lower price product to meet the development of our four-modernization, but also bring many job opportunities to people, tax to government, and integrate the rural and urban area output to increase effectively. There are three types of auto parts makers. They are OEM auto parts supplier, Exporter and Aftermarket supplier. To compete with the local marketer, E-business has being seen as a good channel to improve the current situation and increase competitive advantage for many wholesaler by lowering the cost and increasing high-speed response to customers. Therefore, this study would like to seek some relationship and advantages of using E-business to explore general extent of the impact of E-business towards China auto parts wholesale markets, investigate offline and online strategies, and how wholesale companies exploit synergies from the coordination of electronic and physical channel.